Perbandingan Sifat Mekanis Material Logam dalam Industri Manufaktur - Zandroto, Dian Ayu Aulia; Naim, Raihan Deprija; Riawan, Ibnu Azmi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This research aims to analyze the mechanical properties of metal materials produced using various manufacturing techniques, both conventional and additive manufacturing (AM) technologies such as SLM, WAAM, and EBM. The main focus of this study is to evaluate the influence of microstructure and porosity on the tensile strength, stiffness, ductility, and fatigue resistance of these materials. The research method used is a comparative experimental study, collecting data from the latest literature and laboratory test results on materials such as high-strength steel, aluminum alloys, and composites. Research findings indicate that the use of innovative materials can improve production efficiency and vehicle performance, with some AM materials exhibiting higher strength despite a sacrifice in flexibility. The recommendation for this research is to optimize material selection based on application and more efficient manufacturing processes.